Tectonic inversion of the Dnipro-Donets basin. Part 3. Tectonic style of deformations - Oleksii Bartaschuk; Vasyl Suyarko; Oleksandr Chuienko (Вісник Харківського національного університету імені В.Н. Каразіна. Серія Геологія. Географія. Екологія, 2023)
The purpose. The peculiarities of the spatial distribution and tectonic style of collisional deformations of the riftogenic structure of the Dnipro-Donets Basin were investigated.